2020
DOI: 10.4236/ojpsych.2020.104017
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy for Adults with ADHD during COVID-19: An Open Trial

Abstract: This exploratory study reports the outcomes of a remotely delivered manualised form of Acceptance and Commitment Therapy (ACT) to adults with Attention Deficit Hyperactivity Disorder (ADHD) during the COVID-19 imposed "lockdown". Adults completing this intervention (N = 12) reported statistically and clinically significant improvements on outcomes relating to self-reported mood F(1.356, 14.917) = 21.64, p < 0.001, η 2 = 0.66), anxiety F(2, 22) = 22.93, p < 0.001, η 2 = 0.68), psychosocial adjustment (χ 2 (4) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A total of 12 adults with ADHD were recruited and three sessions of a manualised form of ACT was delivered remotely via telephone and video conferencing followed by a two-week follow-up. The findings demonstrated that the cost-effective and remotely administered ACT was an adequate way to sustain the mental health and adjustment of adults having ADHD during future COVID-19 or other epidemic-related-lockdowns ( Fullen et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 12 adults with ADHD were recruited and three sessions of a manualised form of ACT was delivered remotely via telephone and video conferencing followed by a two-week follow-up. The findings demonstrated that the cost-effective and remotely administered ACT was an adequate way to sustain the mental health and adjustment of adults having ADHD during future COVID-19 or other epidemic-related-lockdowns ( Fullen et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, substantial improvements were found on measures associated to self-reported mood, anxiety, psychosocial adjustment and treatment acceptability was good ( Fullen et al., 2020 ). Likewise, another study evaluated the viability of ACT among school-going individuals with comorbid ADHD, learning disorders, and disruptive behavior issues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations